Direct Keap1-Nrf2 disruption as a potential therapeutic target for Alzheimer's disease. - Fiona Kerr; Oyinkan Sofola-Adesakin; Dobril K Ivanov; Jemma Gatliff; Beatriz Gomez Perez-Nievas; Hélène C Bertrand; Pedro Martinez; Rebecca Callard; Inge Snoeren; Helena M Cochemé; Jennifer Adcott; Mobina Khericha; et al. (PLoS Genetics)
Nrf2, a transcriptional activator of cell protection genes, is an attractive therapeutic target for the prevention of neurodegenerative diseases, including Alzheimer's disease (AD). Current Nrf2 activators, however, may exert toxicity and pathway over-activation can induce detrimental effects. An understanding of the mechanisms mediating Nrf2 inhibition in neurodegenerative conditions may therefore direct the design of drugs targeted for the prevention of these diseases with minimal side-effects. Our study provides the first in vivo evidence that specific inhibition of Keap1, a negative regulator of Nrf2, can prevent neuronal toxicity in response to the AD-initiating Aβ42 peptide, in correlation with Nrf2 activation. Comparatively, lithium, an inhibitor of the Nrf2 suppressor GSK-3, prevented Aβ42 toxicity by mechanisms independent of Nrf2. A new direct inhibitor of the Keap1-Nrf2 binding domain also prevented synaptotoxicity mediated by naturally-derived Aβ oligomers in mouse cortical neurons. Overall, our findings highlight Keap1 specifically as an efficient target for the re-activation of Nrf2 in AD, and support the further investigation of direct Keap1 inhibitors for the prevention of neurodegeneration in vivo.